Clothing Designs Based on the Buttoning and Unbuttoning Abilities of Children - OKADA, Nobuko (Journal of Home Economics of Japan, 1996)
This study has been carried out to help design garments that encourage children to develop self-dressing skills. Buttons need to be easily manageable for pre-school children. In order to understand the learning process of buttoning and unbuttoning, a boy was longitudinally observed, once every 3 days, from the age of 9 months to the age of 3 years and 4 months. The learning processes of another thirty-eight pre-school children were recorded cross-sectionally on video-tape. The buttoning and unbuttoning time data for pre-school children were also gathered. It was found that easily grasped, flat buttons with a 2 cm diameter were most suitable. Further, to accommodate this button size, it is recommended that the buttonhole size be 4 mm larger than normal. Pre-school children can button and unbutton fastest when the color of the buttons is easily distinguishable from the color of their clothing. All the buttons should be placed in visible positions, with the top button being about 7.5 cm below the fossa jugularis. Children with developed dressing skills are able to button and unbutton without looking at the buttons. Children who have reached the age of 5 are normally able to complete the buttoning and unbuttoning process by themselves.